Low and high frequency isometric handgrip exercise training similarly reduce resting blood pressure in young normotensive adults: A randomised controlled trial - BENJAMIN MCNALLY (Journal of Sports Sciences, 2025)
We investigated the effects of low and high frequency isometric handgrip exercise training (IHGT) on resting blood pressure, and the affective/perceptual responses during training. Sixty young normotensive adults were randomised to either a no-intervention control group (CON: n = 20; 12 female) or a group performing either two (LOW: n = 20; 18 female) or four (HIGH: n = 20; 13 female) sessions/week of IHGT for 4 weeks. IHGT involved 4 × 2-min holds at 30% maximal voluntary contraction using the dominant hand. Resting blood pressure was measured before and after training. Affective valence was measured during the first session of each training week. Systolic blood pressure was reduced following both LOW (adjusted mean change [95% CI]: −4.5 [−6.8, −2.2] mmHg) and HIGH (−5.3 [−7.6, −3.0] mmHg) frequency IHGT groups compared to CON (+0.5 [−1.8, 2.8] mmHg; p < 0.01), with no difference between LOW and HIGH. There were no changes in diastolic blood pressure. During the first session, affective valence decreased by 2.5 ± 2.6 units and became negative (lowest affect: −0.75 ± 1.84 units). However, affective responses improved as training progressed. Low and high frequency IHGT similarly reduce resting blood pressure in young normotensive adults. Negative affective responses in the early phase of training improve as the intervention progresses.